Investigating awareness issues with Agile practices - Sulaiman, N. L. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper presents on awareness issues among agile practitioners in implementing agile software development methodology. Data were collected from 36 respondents using a quick survey of agile practitioners at Agile Malaysia events. The results revealed the awareness problems affect the productivity of agile practitioners in implementing agile practices and misuse the agile practices. There are needs of investigating the awareness issues to gain better understanding in agile implementation as awareness is an initial step for agile practitioners to implement agile practices in proper way.